2016
DOI: 10.1039/c6nj02018f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of ferrocene amides and esters from aminoferrocene and 2-substituted ferrocenecarboxylic acid and properties thereof

Abstract: International audienceDifferent ferrocenecarboxamides were synthesized from aminoferrocene and various acid coupling partners such as N-alpha-Boc-L-tryptophan and N-protected sugar amino acids ( N-Boc-3-amino-3-deoxy-1,2-O-isopropylidene-alpha-D-ribofuranoic acid, N-Boc-3-amino-3-deoxy-1,2-O-isopropylidene-alpha-D-xylofuranoic acid and their corresponding homo- and hetero-dimers). Similarly, reactions between 2-aminoethyl ferrocenecarboxylate and N-protected sugar amino acids afforded compounds with a carboxam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…1 41 Microanalyses were performed on a Flash 1112 Thermo Fisher elemental analyzer. Iodoferrocene, 42 2-iodobenzothiophene, 43 2iodobenzofuran 43 and 2-iodofuran 44 were prepared as described previously.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…1 41 Microanalyses were performed on a Flash 1112 Thermo Fisher elemental analyzer. Iodoferrocene, 42 2-iodobenzothiophene, 43 2iodobenzofuran 43 and 2-iodofuran 44 were prepared as described previously.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This has been realized by Nassar, Erb, Radha Krishna et al, who transformed 2iodoferrocenecarboxylic acid (110), in racemic (rac-110) as well as in enantiopure form [(S p )-110] into the ester 111, from which the Boc-protected ferrocenyl-1,2-dicarboxylate 112 was obtained in the presence of 0.8 equivalents of copper (I) oxide in 54% yield in racemic as well as in enantiopure form (Scheme 36). 72 More recently, Csámpai et al reported a related reaction in which a sulfur atom was attached to the ferrocene moiety via an intramolecular reaction. In the intramolecular substitution, thioamides such as 113 were converted into ferrocenothiazines like 114 in up to 93% yield in the presence of copper(I) iodide and N,N′-dimethylethylenediamide (DMEDA) (10 mol% each) (Scheme 37).…”
Section: Scheme 35 Syntheses Of Ferrocenyl Acetates From Iodoferrocenmentioning
confidence: 99%
“…Indeed, whereas iodoferrocene can react with amides by recourse to copperbased systems, [16] the involvement of 2-substituted derivatives in such couplings is far less obvious due to competitive deiodination. [16c] While continuing our work dedicated to the synthesis of ferrocene amides, [17] we recently reported the successful N-arylation using iodoferrocene of a large range of carboxamides. [18] In the continuation of our efforts to develop synthetic methods in the ferrocene series and to understand their specific behavior, [17,19] we were eager to study the effect of an additional substituent at the 2-, 3-or 1'-position of iodoferrocene on the amide N-arylation.…”
Section: Introductionmentioning
confidence: 99%
“…[16c] While continuing our work dedicated to the synthesis of ferrocene amides, [17] we recently reported the successful N-arylation using iodoferrocene of a large range of carboxamides. [18] In the continuation of our efforts to develop synthetic methods in the ferrocene series and to understand their specific behavior, [17,19] we were eager to study the effect of an additional substituent at the 2-, 3-or 1'-position of iodoferrocene on the amide N-arylation. To this goal, 35 substituted iodoferrocenes were engaged in the copper-mediated N-arylation reaction, leading to 28 original N-ferrocenyl acetamides, isolated in moderate to good yields which were tentatively linked to the structural and electronic features of the iodo partners.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation